2023
DOI: 10.3389/frwa.2022.966223
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing drivers of widespread colonization of Legionella pneumophila in a green building: Roles of water softener system, expansion tank, and reduced occupancy

Abstract: IntroductionLegionella pneumophila is an opportunistic pathogen that is a key contributor to drinking water-associated disease outbreaks in the United States. Prolonged water stagnation periods in building plumbing systems due to low occupancy, especially during building shutdowns, breaks, and holidays, can lead to water quality deterioration and (re)colonization of buildings with L. pneumophila. Water monitoring in buildings typically relies on grab samples with small datasets.MethodsIn this study, a larger d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Building AZ-1 (Legiolert positivity: 100% [ n = 7 of 7]; qPCR positivity: 100% [ n = 7 of 7]) uses a whole-building water softening system that treats water upon entry into the building. Samples collected from the water entry point revealed that the inlet water was Legiolert-negative and contained a chlorine residual of 0.59 mg L −1 as Cl 2 , 53 whereas the sample from the water storage tank immediately after the softener was positive for L. pneumophila by both Legiolert (10 616 MPN L −1 ) and qPCR (650 gc L −1 ) and had a low chlorine residual (0.05 mg L −1 as Cl 2 ). These results indicate that residual disinfectant loss was occurring in the water softener and storage tank.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Building AZ-1 (Legiolert positivity: 100% [ n = 7 of 7]; qPCR positivity: 100% [ n = 7 of 7]) uses a whole-building water softening system that treats water upon entry into the building. Samples collected from the water entry point revealed that the inlet water was Legiolert-negative and contained a chlorine residual of 0.59 mg L −1 as Cl 2 , 53 whereas the sample from the water storage tank immediately after the softener was positive for L. pneumophila by both Legiolert (10 616 MPN L −1 ) and qPCR (650 gc L −1 ) and had a low chlorine residual (0.05 mg L −1 as Cl 2 ). These results indicate that residual disinfectant loss was occurring in the water softener and storage tank.…”
Section: Resultsmentioning
confidence: 99%
“…34 Investigations into the impact of COVID-19 pandemicrelated building closures have reported that building water quality overall was negatively impacted. [45][46][47][48][49][50][51][52][53] However, studies have reported mixed results with respect to L. pneumophila, including no or low detection of L. pneumophila, 45,50,52 no change in the occurrence of L. pneumophila as water use returned to normal levels, 46 a small increase (2×) in Legionella spp. relative abundance after two months of reduced water use, 48 and widespread detection of L. pneumophila that increased during closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. pneumophila has been identified in green buildings as a high concern. [10][11][12] While microbial risks often drive water safety considerations due to their acute effects, chemical constituents are also important health concerns. Small diameter pipes and low flow fixtures potentially accelerate the accumulation of both chemical and microbial contaminants and can promote biofilm growth in premise plumbing.…”
Section: Introductionmentioning
confidence: 99%
“…In multiple Italian hotel buildings, soft water was correlated with L. pneumophila levels . Elsewhere, building water softeners reduced disinfectant residual concentration and contributed to increased faucet L. pneumophila and disinfection byproduct levels. Resins can exert a free chlorine demand . The regeneration process can decrease microorganism concentrations, and pathogenic bacteria can remain in the softener even after regeneration .…”
Section: Introductionmentioning
confidence: 99%